Determining the effectiveness of oar blades in rowing - Kleshnev V.V. ,; Andreeva E.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the main theoretical principles and measurement methods and provide practical examples of how to correctly determine the efficiency of a rowing blade in academic rowing. Methods and structure of the study. A telemetric system was used for measurement, which allows for accurate measurement of effort, oar angles and boat movement, and uses this data to reconstruct the trajectory of the oar in the water during the stroke. Results and conclusions. On average, the hydro-lift force provides about 56% of the total force on the blade, and the drag force provides the remaining 44%. The total drift of the blade center along its curved trajectory is 1.7 m, and the total blade efficiency is 80.5%. The oar blade is a fairly efficient propulsion device compared to the 24% average physiological efficiency of a rower. Therefore, of all the metabolic energy consumed by the athlete, less than 6% is lost to blade drift, and most of it is dissipated as heat in the rower's body. The blade's efficiency was higher at the beginning and end of the stroke, so it is advantageous to quickly increase the effort after the catch and maintain it longer at the end, in other words, to make the effort curve more rectangular. This is also useful for both overall power and the effective dynamics of the rowing system.